HARMONI PASANGAN PERNIKAHAN SIRI (The Harmony of Siri Marriage Couple) - Alifa Ashadiyah Dimastiwi (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
Siri (underhand) marriage, although it has a negative impact particularly on women and children, is still found widely in Indonesia, including in Sumberglagah Village, Rembang District, Pasuruan Regency, East Java. This paper will discuss how the Siri marriage household in Sumberglagah Village can run harmoniously. This study used a qualitative research method with three informants consisting of two women and one man who were married in underhand manner (siri). Siri marriages carried out by residents of Sumberglagah Village occur for several reasons: they consider Siri is legal in Islam, the marriage process is faster than being legally registered at the KUA, mutual need for one another, and to ensure the necessities of life, especially for women with low education levels. Keywords: marriage, unregistered marriage, Sumberglagah village